Ritual in Late Bronze Age Ireland : material culture, practices, landscape setting and social context - Leonard, Katherine (Archaeopress Publishing Ltd, 2015)
This text develops a new perspective on Late Bronze Age (LBA) Ireland by identifying and analysing patterns of ritual practice in the archaeological record. The bookends of this study are the introduction and proliferation of iron technology beginning around 600 BC. Therefore, it is societal change related to new technology which defines the period discussed as the Irish Late Bronze Age (LBA) herein.